Disposal Options of Bamboo Fabric-Reinforced Poly(Lactic) Acid Composites for Sustainable Packaging: Biodegradability and Recyclability - M.R., Nurul Fazita; Jayaraman, Krishnan; Bhattacharyya, Debes; Hossain, Md. Sohrab; M.K., Mohamad Haafiz; H.P.S., Abdul Khalil (MDPI, 2015)
The present study was conducted to determine the recyclability and biodegradability of bamboo fabric-reinforced poly(lactic) acid (BF-PLA) composites for sustainable packaging. BF-PLA composite was recycled through the granulation, extrusion, pelletization and injection processes. Subsequently, mechanical properties (tensile, flexural and impact strength), thermal stability and the morphological appearance of recycled BF-PLA composites were determined and compared to BF-PLA composite (initial materials) and virgin PLA. It was observed that the BF-PLA composites had the adequate mechanical rigidity and thermal stability to be recycled and reused. Moreover, the biodegradability of BF-PLA composite was evaluated in controlled and real composting conditions, and the rate of biodegradability of BF-PLA composites was compared to the virgin PLA. Morphological and thermal characteristics of the biodegradable BF-PLA and virgin PLA were obtained by using environment scanning electron microscopy (ESEM) and differential scanning calorimetry (DSC), respectively. The first order decay rate was found to be 0.0278 and 0.0151 day1 in a controlled composting condition and 0.0008 and 0.0009 day1 in real composting conditions for virgin PLA and BF-PLA composite, respectively. Results indicate that the reinforcement of bamboo fabric in PLA matrix minimizes the degradation rate of BF-PLA composite. Thus, BF-PLA composite has the potential to be used in product packaging for providing sustainable packaging.